The Potential Use of Ground Ceramic Tile Waste as Partial Cement Replacement in Mortar - Muthusamy, Khairunisa; Tanash, Alaa Omar; Ismail, Mohamed A. Ismail; Othman, Nor Hazurina (International Journal of Sustainable Construction Engineering and Technology, 2025)
In line with sustainable development goals, waste generated from the construction industry that increases annually need to be well managed to ensure environmental sustainability. Ceramic waste is type of solid waste generated at construction site and disposed at landfill which contribute towards environmental pollution. The present research investigates the effect of ground ceramic tile as a partial cement replacement on properties of mortar. Six mixes consisting 0%, 10%, 20%, 30%, 40%, and 50% of ceramic tile powder by weight of cement were tested. The mixes were subjected to setting time test, flow table test, compressive strength and water absorption test. Inclusion of tile powder up to 50% increases the final setting time, but not more than 6.5 hours. Upon blending 10% and 20% tile powder, the flowability value of mortar mixture reduced slightly from 190mm to 185mm and 180mm respectively. The inclusion of 20% tile powder produces mortar with compressive strength of 39.50MPa due to the pozzolanic reaction of the powder. Success in integrating ceramic tile waste as cement replacement would reduce quantity of waste disposed and promotes a cleaner environment.